Program Pengembangan Desa Mitra Siaga Komorbid Era New Normal di Wilayah Kerja Puskesmas Jambi Kecil - Arvida. Bar; Kaimuddin Kaimuddin; Nur Insani (Jurnal Abdimas Kesehatan (JAK), 2022)
In this normal new era, where comorbid is in the spotlight due to the death rate of Covid-19 disease is usually accompanied by the condition of a heretic. Proper methods of controlling and cutting off the chain of infection can include 3M (wearing masks, washing hands, walking distance) in everyday life. The goal of creating a partnership between stakeholders (center head, village head), is to increase knowledge of education and training of cadence and health-care professionals. It was supported by village headmen center chiefs and community leaders. It also greatly helps communities learn about their health and condition during the Covid-19 pandemic and increases their understanding in efforts to prevent the spread of Covid-19 diseases in society. The results of an evaluation of improved public knowledge assessment and Kader. Assessments from the questionnaires are shown increasing knowledge from communities impervious to land dung, waterproofing daffs, and lakes. The devotion of this society resulted in increased knowledge and attitude in the pathological and societal preparedness of the Covid-19 infection in the region of the minor Jambi office, the increased behavior of Kader to try together to prevent the transmission of Covid-19 especially to the morphing grouping of the groupings in the impervious aged lake village, land retards, and refunds.